Multiple intelligences related to the Common National Curriculum Fields of Experience in Early Childhood Education (Research, Society and Development, 2020)
Early childhood education is an important phase in the child's life to develop the matrices of knowledge and to understand it as a culture system in which it is inserted. In this scenario, the teacher will be highlighted with emphasis on the conception of promoting the education of the child. children through activities that consider the lived world of the students, their stories, their family, their colleagues, with whom they live, both at the institution and at home. From this contextualization, it is intended to contribute to the context of early childhood education in order to highlight the possible relationship between the Multiple Intelligences (IM) and the Fields of Experience of the Common National Curriculum (BNCC). The main objective of this article is to describe the Theory of Multiple Intelligences and to relate them to the Fields of Experience of the Common National Curriculum (BNCC). The methodological approach is qualitative and relates the Howard Gardner Multiple Intelligence Theory and the BNCC National Curriculum Fields of Experience (BRAZIL, 2017). It was inferred that the intelligences manifest in all people, and their development is also related to the stimuli that are recommended in the five fields of experience of the Common National Curriculum Base - BNCC (BRAZIL, 2017) and its development of early childhood education.